Interpreting roof extensometry in coal mine roofs. Issue 3 (3rd July 2019) - Seedsman, Ross
ABSTRACT: When the displacement at the roof line is greater than about 40 mm, extensometry in the immediate roof of coal mine roadways reveals similar displacement patterns. The deformation within the roof can be characterised by a linear bulking factor in the order of 1–3%. It is suggested that this bulking can be interpreted to be the result of the volume increase after brittle failure. Bulking factors increase with the height of brittle failure and this may be related to the greater horizontal closure to which the failed material is exposed. Displacement triggers used to manage the stability of the roadways can be related to the onset of brittle failure. Modelling of the straining of a jointed bedded rock mass suggests the development of localised shear and dilational deformations of up to 90 mm which could cause the failure of fully grouted cables.